Hoja Arif Raugari (1165-1262) priest of the Nakhishbandi orden and his religious and ethical conclusions in the treatise «Arifnama» (Journal of Philosophy Culture and Political Science, 2023)
The article tells about the life and work and religious views of Hoja Arif Raugari, the 2nd priest of the Khojagan community in the initial period of the existence of the Nakhishbandiyya sect, which occupies an important place in the religious life of Central Asia. Hoja Arif Raugari is a man who lived in a very difficult period. His youth coincided with the heyday of the Karakan era. After that, the Seljuks, Karakhits, Khorezm Shah were destined to end their lives in the Shagatai Empire, which was formed in Central Asia after the invasion of Genghis Khan. Although the political situation in the era in which he lived was turbulent, he made the spiritual core of his life the Sufi teachings that he learned from his teacher Abdukhalyk Gyzduani (1st pir of the Khojagan sect). Along the way, he searched and sweated day and night. Sufism did psychotechnical exercises and tried to manifest itself in the dance of piety. His diligence was justified, and with the permission of his teacher Abdukhalyk Gizduani, he took over the reins of the Khojagan community. To set an example for his students, he wrote a treatise called Arifnama. The «Arifname» reflects the prerequisites for a deep study of the Sufi teachings, the methodology for crossing the layers of spirituality. In particular, the spiritual foundations and stages of the path to the Truth (sair-suluk), the place of Sharia in Sufism, the status of scientists and guardians, customs, etc. He made new connections with his experiences about the spiritual principles of perfection. In this study, along with the life of Hoja Arif Raughari, the treatise «Arifnam» and his Sufi views will be scientifically analyzed.Key words: sheikh, caliph, sharia, tariqa, salih, sair-suluk, arif, saint.